The little prince - Ellams, Inua (Oberon modern plays., 2020)
"Broken down in the Sahara Desert, desperate to repair her fighter jet, a pilot meets an extraordinary Little Prince. As he recounts his adventures, the pilot re-discovers the power of belief, the importance of doing what we can to protect our natural world, and the true meaning of friendship. In Inua Ellams' magical retelling of the much loved story by Antoine de Saint-Exupéry, the Little Prince descends from an African race in a parallel galaxy. He travels across time and space seeking help to bring peace to his warring planet. His journey as a galactic emigrant addresses climate change, morality, takes us through solar systems of odd planets with strange beings, and shows how even a little thing can make a big difference."--Back cover.